Ultrasound and Carotid Bifurcation Atherosclerosis - Nicolaides, Andrew; Beach, Kirk W.; Kyriacou, Efthivoulos; Pattichis, Constantinos S.; SpringerLink (Online service) (London : Springer London, 2012)
Ultrasound and Carotid Bifurcation Atherosclerosis provides a comprehensive overview of the most recent advancements in instrumentation, imaging techniques including the use of contrast enhancement agents, plaque image analysis and its automation, elastography and plaque motion analysis; also, the use of ultrasonic and other biomarkers in the detection of the high risk cardiovascular individual. Finally, it deals with the application of IVUS, TCD and carotid plaque characterization in clinical practice and in stroke risk stratification. Ultrasound and Carotid Bifurcation Atherosclerosis is intended for all those working in the field of atherosclerosis, ultrasound imaging and cardiovascular risk, including the clinician, the vascular ultrasonographer, the epidemiologist, the molecular biologist, the biomedical engineer and the informatics scientist. Furthermore, this book bridges the gap between the researcher and the clinician, who is keen to incorporate the latest results of research to his daily practice.
Stable and Vulnerable Atherosclerotic Plaques -- Pathophysiology of Carotid Atherosclerosis -- Vascular Hemodynamics of the Carotid Bifurcation and Its Relation to Arterial Disease -- The Problem with Asymptomatic Carotid Stenosis -- Principles of Ultrasonic Imaging and Instrumentation -- Despeckling -- Vascular Ultrasound Imaging with Contrast Agents: Carotid Plaque Neovascularization and the Hyperplastic Vasa Vasorum Network -- Nonlinear Contrast Intravascular Ultrasound -- Molecular Imaging of Carotid Plaque with Targeted Ultrasound Contrast -- Methodological Considerations of Ultrasound Measurement of Carotid Artery Intima-Media Thickness and Lumen Diameter -- Automated Measurement of Carotid Artery Intima-Media Thickness -- Image Normalization, Plaque Typing and Texture Feature Extraction -- Automated Classification of Plaques -- Plaque Feature Extraction -- Plaque Classification -- Volumetric Evaluation of Carotid Atherosclerosis Using 3-Dimensional Ultrasonic Imaging -- Carotid Plaque Surface Irregularity -- Carotid Plaque Texture Analysis Using 3-Dimensional Volume Ultrasonic Imaging -- Wall Motion Analysis -- Noninvasive Carotid Elastography -- Motion Estimation of Carotid Artery Plaques -- Carotid Intima-Media Thickness Measurement: A Suitable Alternative for Cardiovascular Risk? -- Intima-Media Thickness and Carotid Plaques in Cardiovascular Risk Assessment -- Association Between Plaque Size, Growth and Echogenicity with Cardiovascular Risk: The Tromsø Study -- Towards Clinical Applications of Carotid Ultrasound: Intima-Media Thickness, Plaque Area, and 3-Dimensional Phenotypes -- Arterial Wall, Plaque Measurements, Biomarkers and Metabolic Syndrome: Results from the Gothenburg Studies -- Novel Biomarkers and Subclinical Atherosclerosis -- Subclinical Atherosclerosis, Markers of Inflammation and Oxidative Stress -- Screening for Cardiovascular Risk Using Ultrasound: A Practical Approach -- Grading Internal Carotid Artery Stenosis -- The Significance of Echolucent Plaques: Past and Future Perspectives -- Intravascular Ultrasound: Plaque Characterisation -- Gray-Scale Based Stratified Color Mapping of Carotid Plaque -- Transcranial Doppler and Cerebrovascular Risk Stratification in Patients with Internal Carotid Artery Atherosclerosis -- Effect of Statin Therapy on Carotid Plaque Morphology -- Image Analysis of Carotid Plaques and Risk Stratification -- Ultrasonic Plaque Characterization: Results from the Asymptomatic Carotid Stenosis and Risk of Stroke (ACSRS) Study.
Keywords: Medicine; Radiology, Medical; Diagnosis, Ultrasonic; Cardiology; Vascular Surgery; Medicine & Public Health; Cardiology; Ultrasound; Imaging / Radiology; Vascular Surgery